Self-Managed Teams - Messinis, Anne-Marie (Revue YOUR Review (York Online Undergraduate Research), 2017)
A self-managed team is defined as an autonomous group of individuals who carry forth a common goal in the absence of a formal leader. In this team configuration, members are given the collective authority to form their own practices and day-to-day processes. An effective self-managed team will have proactive coordination amongst their members to successfully take on the responsibility usually left to a leader. Like any team arrangement, self-managed teams have both benefits and challenges. Therefore, it is imperative for organizations to understand the fundamental functions of self-managed teams and how to utilize them to their greatest potential. This research project discusses the most prominent issues facing self-managed teams, and draws on various theoretical perspectives and empirical studies. These issues include: control, equal contribution, trust, and leadership. The study offers a list of recommendations detailing how organizations can effectively resolve and prevent those four issues from occurring in their own self-managed teams.